Branding Image of Higher Education Quality Based on Islamic Boarding Schools - Khoiroh, Muhimmatul; Aziz, Abd.; Fatimah, Nur (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study aims to describe the branding image development strategy of Islamic boarding school-based higher education. The study elevates the branding